Legal Position of Restorative Justice Enforcement in Indonesia - Amrizal, Amrizal; Sara, Rineke (Indonesian Journal of Multidisciplinary Science, 2025)
This study explores the legal position and implementation of restorative justice in Indonesia as a progressive approach to criminal law reform. Initially introduced through Law No. 11 of 2012 concerning the Juvenile Criminal Justice System, restorative justice emphasizes the involvement of victims, offenders, and the community in resolving criminal cases with a focus on restoration rather than retribution. Although its application has gradually expanded to adult offenders, it remains partially regulated and lacks a comprehensive statutory foundation. This paper applies a qualitative method using a normative juridical and descriptive-analytic approach, based on legal materials, statutory provisions, and institutional regulations. The findings reveal that restorative justice in Indonesia has not yet been codified into a single unified law. Instead, its practice is fragmented across various institutional regulations, such as those issued by the Indonesian National Police, the Attorney General's Office, and the Supreme Court. The study highlights several issues, including the inconsistent application of restorative justice, the persistence of retributive legal culture among victims, and the urgent need to reduce prison overcrowding. It argues that restorative justice offers an effective alternative to imprisonment by promoting conflict resolution, victim-offender reconciliation, and community-based justice. The incorporation of restorative justice into Indonesia’s Draft Criminal Code and institutional frameworks signifies a growing shift toward legal modernization, social justice, and the realization of Pancasila-based values in the national penal system.